Quadriceps and Patellar Tendon Thickness and Stiffness in Elite Track Cyclists: An Ultrasonographic and Myotonometric Evaluation - Klich, Sebastian; Ficek, Krzysztof; Krymski, Igor; Klimek, Andrzej; Kawczyński, Adam; Madeleine, Pascal; Fernández-de-las-Peñas, Cesar (Frontiers in Physiology, 2020)
Track cyclists are required to perform short- and long-term efforts during sprint and endurance race events, respectively. The 200 m flying sprint races require maximal power output and anaerobic capacity, while the 4000 m pursuit cyclists demand a high level of aerobic capacity. Our goal was to investigate spatial changes in morphological and mechanical properties displayed using 3D topographical maps of the quadriceps muscle and tendons after 200 m flying start and 4000 m individual pursuit race in elite track cyclists. We hypothesized a non-uniform distribution of the changes in the quadriceps muscle stiffness (QMstiff), and acute alterations in quadriceps tendon (QTthick) and patellar tendon (PTthick) thickness. Fifteen men elite sprint and 15 elite men endurance track cyclists participated. Sprint track cyclists participated in a 200m flying start, while endurance track cyclists in 4000 m individual pursuit. Outcomes including QTthick (5-10-15mm proximal to the upper edge of the patella), PTthick (5-10-15-20mm inferior to the apex of the patella) – using ultrasonography evaluation, QMstiff, and quadriceps tendon stiffness (QTstiff) were measured according to anatomically defined locations (point 1-8) and patellar tendon stiffness (PTstiff) – using myotonometry, measured in a midway point between the patella distal and the tuberosity of tibial. All parameters were assessed before and after (up to 5 min) the 200 m or 4000 m events. Sprint track cyclists had significantly larger QTthick and PTthick than endurance track cyclists. Post-hoc analysis showed significant spatial differences in QMstiff between rectus femoris, vastus lateralis, and vastus medialis in sprint track cyclists. At before race, sprint track cyclists presented significantly higher mean QTthick and PTthick, and higher QMstiff and the QTstiff, as compared with the endurance track cyclists. The observed changes in PTThick and QTThick were mostly related to adaptation-based vascularity and hypertrophy processes. The current study suggests that assessments using both ultrasonography and myotonometry provides crucial information about tendons and muscles properties and their acute adaptation to exercise. Higher stiffness in sprint compared with endurance track cyclists at baseline seems to highlight alterations in mechanical properties of the tendon and muscle that could lead to overuse injuries.